Effect of dialysate buffer practices on serum parathyroid hormone concentrations in real-life french patients receiving hemodialysis - Pablo Antonio Ureña Torres; Moustafa Naja; Minh Hoang Tran; Martine Cohen-Solal; Jordi Bover; Anne Kolko; Pascal Seris; Ibrahim Farah; Natalia Alençar-de-Pinho; Ziad A. Massy; Charles Chazot (PLoS ONE, 2026)
Background Dialysate composition is crucial for managing secondary hyperparathyroidism (SHPT) in patients on hemodialysis. Acetate‐based dialysates elevate serum acetate and trigger adverse effects, while citrate and hydrochloric acid formulations might offer distinct clinical benefits. Methods In this longitudinal observational real-life study, 876 adult patients on hemodialysis were classified by acid component of the dialysate (acetic acid, citric acid, or hydrochloric acid). Monthly pre-dialysis parathyroid hormone (PTH) and bone-mineral biomarkers were measured. A linear mixed model (LMM), adjusted for baseline PTH, demographics, and clinical covariates, evaluated PTH trajectories over two years. The significance of the main effect of dialysate and its interaction with time was assessed using likelihood-ratio tests (LRT). Results At baseline, serum PTH was significantly higher in the acetate group. The LMM confirmed significant influence of dialysate type (p < 0.001) and its interaction with time (p = 0.048) on PTH trajectories. Over two years, acetate showed a modest, non-significant PTH reduction of 2.9% (95% CI: −8.8% to +3.4%), whereas hydrochloric acid resulted in a significant cumulative PTH reduction of 10.9% (95% CI: −15.7% to −0.2%), with a significantly different yearly slope versus acetate (p = 0.044). Citrate showed a modest, non-significant change compared to acetate (−2.3%; 95% CI: −6.7% to +8.4%). Baseline PTH, phosphate, prior hypercalcemia, and dialysate calcium concentration were major predictors in the model. Conclusions In adjusted longitudinal analyses, hydrochloric acid–based bicarbonate dialysate was associated with a steeper decline in pre-dialysis PTH over two years compared with acetate, while citrate did not differ from acetate. Prospective studies are needed to confirm whether buffer composition influences PTH control under standardized calcium-bath strategies.